Evaluation of a propolis water extract using a reliable RP-HPLC methodology and in vitro and in vivo efficacy and safety characterisation - Rocha, Bruno Alves; Bueno, Paula Carolina Pires [UNESP]; Vaz, Mirela Mara de Oliveira Lima Leite; Nascimento, Andresa Piacezzi; Ferreira, Nathália Ursoli; Moreno, Gabriela de Padua; Rodrigues, Marina Rezende; Costa-Machado, Ana Rita de Mello; Barizon, Edna Aparecida; Campos, Jacqueline Costa Lima; De Oliveira, Pollyanna Francielli; Acésio, Nathália de Oliveira; et al. (My University, 2013)
Since the beginning of propolis research, several groups have studied its antibacterial, antifungal, and antiviral properties. However, most of these studies have only employed propolis ethanolic extract (PEE) leading to little knowledge about the biological activities of propolis water extract (PWE). Based on this, in a previous study, we demonstrated the anti-inflammatory and immunomodulatory activities of PWE. In order to better understand the equilibrium between effectiveness and toxicity, which is essential for a new medicine, the characteristics of PWE were analyzed. We developed and validated an RP-HPLC method to chemically characterize PWE and PEE and evaluated the in vitro antioxidant/antimicrobial activity for both extracts and the safety of PWE via determining genotoxic potential using in vitro and in vivo mammalian micronucleus assays. We have concluded that the proposed analytical methodology was reliable, and both extracts showed similar chemical composition. The extracts presented antioxidant and antimicrobial effects, while PWE demonstrated higher antioxidant activity and more efficacious for the most of the microorganisms tested than PEE. Finally, PWE was shown to be safe using micronucleus assays. © 2013 Bruno Alves Rocha et al.
Keywords: propolis; animal experiment; antimicrobial activity; antioxidant activity; controlled study; drug efficacy; drug safety; drug screening; genotoxicity; in vitro study; in vivo study; male; micronucleus test; nonhuman; priority journal; rat; reversed phase high performance liquid chromatography